Utilization of VBA Excel-Based Virtual Laboratories in Kinematics and Dynamics Learning - Muhammad Akbar; Indah Slamet Budiarti (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2023)
The purpose of this community service activity is to mentor students and teachers in schools in using virtual laboratories. In this case the Excel VBA application is used in its application to kinematics and dynamics material. This activity was carried out at SMAN 1 Kemtuk Gresi, Jayapura Regency. Submission of material is equipped with a practicum module based on LKPD to make it easier for students and teachers during implementation. In carrying out this community service activity, the enthusiasm of students and teachers was very good. This is because the implementation of virtual and real practicum can add insight in learning physics. Students also just realized that MS Excel can be utilized in physics simulations because their perception so far is that MS Excel is only a program that is used only to input data in tables. The teacher also gave a positive response to the community service activities that had been carried out because it helped in making a VBA Excel-based virtual laboratory and making LKPD.